Ceramic substrate
Patent Information
- Application Number
- CN202580019896.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-21
- Filing Date
- 2025-05-16
- Publication Date
- 2026-10-30
Smart Images

Figure SMS_1
Abstract
Description
[0001] This invention relates to ceramic substrates, methods for obtaining them, and their uses.
[0002] describe
[0003] Ceramic compositions or substrates are widely used as substrates for mounting electronic components via metal layers. In this case, the ceramic composition acts as an insulating layer, upon which a metal layer is disposed. Electronic components can then be mounted on the metal layer.
[0004] Ceramic compositions or substrates used for mounting electronic components require excellent release characteristics, particularly high thermal conductivity. Simultaneously, the ceramic substrate, as a mounting substrate, should possess good mechanical strength. This is especially necessary as the thickness of the ceramic substrate decreases due to the continuous miniaturization of electronic components. Therefore, ceramic substrates need to possess both high thermal conductivity and high mechanical strength.
[0005] The known type of ceramic substrate used in this setup is an alumina substrate containing zirconia (zirconia toughened alumina substrate - ZTA substrate).
[0006] ZTA substrates comprising alumina and zirconia crystal particles are described, for example, in EP 3 786 134 A1. Of all 100% by mass of the components, alumina is provided at 70% by mass or greater and 95% by mass or less, and the total amount of stabilizer components and zirconia (containing hafnium oxide) is provided at 5% by mass or greater and 30% by mass or less. The average equivalent circular diameter of the alumina crystal particles is greater than the average equivalent circular diameter of the zirconia crystal particles, and is 1.2 μm or greater and 1.9 μm or less. Furthermore, in the cumulative distribution of the equivalent circular diameter of the alumina crystal particles, the difference between the equivalent circular diameter at the 10% accumulation point (d10) and the equivalent circular diameter at the 90% accumulation point (d90) is 1.5 μm or greater and 2.5 μm or less.
[0007] Ceramic substrates that meet this configuration offer both high thermal conductivity and high mechanical strength.
[0008] Therefore, the object of the present invention is to provide a ceramic ZTA substrate having good mechanical properties, such as high thermal conductivity and / or good mechanical strength, combined with good adhesion to a metal layer disposed on a ceramic surface, thereby providing a long service life of the metallized ZTA substrate.
[0009] This objective is achieved by the ceramic substrate according to claim 1.
[0010] Therefore, a ceramic substrate is provided, comprising:
[0011] - 70% by weight or more of alumina (Al2O3) based on the total weight of the ceramic substrate.
[0012] - Up to 30% by weight of zirconium dioxide (ZrO2) based on the total weight of the ceramic substrate.
[0013] - Calcium (Ca), sodium (Na) and yttrium (Y).
[0014] - Other elements: silicon (Si) and / or magnesium (Mg).
[0015] - Where the ratio of sodium content to yttrium content is less than 0.03, and the sodium and yttrium contents are calculated based on their oxide compounds (Na2O / Y2O3).
[0016] Ceramic substrates with this composition exhibit unexpectedly good temperature cycling stability, for example, when metallized via DCB. Values measured from -55°C to +150°C show that the temperature cycling stability is >100% compared to the comparative example, preferably >125% compared to the comparative example, and more preferably >150% compared to the comparative example. The higher values of temperature cycling stability result in longer lifespans for the ceramic substrate or electronic components made from metallized ceramic substrates.
[0017] In another embodiment of the invention, the ceramic substrate comprises (by weight % based on the total weight of the ceramic substrate):
[0018] - 75% to 95% by weight, preferably 88% to 93% by weight, more preferably 89% to 91% by weight of alumina.
[0019] - 4% to 14% by weight, preferably 6% to 11% by weight, more preferably 8% to 10% by weight of zirconium dioxide (ZrO2).
[0020] In another embodiment of the invention, the ceramic substrate comprises (by weight % based on the total weight of the ceramic substrate):
[0021] - 0.2% to 0.8% by weight, preferably 0.3% to 0.7% by weight, more preferably 0.4% to 0.6% by weight of yttrium calculated as sesquioxide (Y₂O₃), and
[0022] - 0.01% to 1.0% by weight, preferably 0.02% to 0.5% by weight, more preferably 0.03% to 0.2% by weight of calcium calculated as calcium oxide (CaO).
[0023] In another preferred embodiment of the invention, the ceramic substrate comprises (by weight % based on the total weight of the ceramic substrate):
[0024] - 0.2% to 0.8% by weight, preferably 0.3% to 0.7% by weight, more preferably 0.4% to 0.6% by weight of yttrium calculated as sesquioxide (Y₂O₃), and
[0025] - 1.0% to 0.01% by weight, preferably 0.5% to 0.02% by weight, more preferably 0.2% to 0.03% by weight of calcium calculated as calcium oxide (CaO).
[0026] In another embodiment of the invention, the ceramic substrate comprises (by weight % based on the total weight of the ceramic substrate):
[0027] - 0.1% to 0.5% by weight, preferably 0.2% to 0.4% by weight, more preferably 0.25% to 0.35% by weight of silicon dioxide (SiO2), and
[0028] - Less than 0.02% by weight, preferably less than 0.01% by weight, of sodium as sodium oxide (Na2O).
[0029] In another preferred embodiment of the invention, the ceramic substrate comprises (by weight % based on the total weight of the ceramic substrate):
[0030] - 0.1% to 0.5% by weight, preferably 0.2% to 0.4% by weight, more preferably 0.25% to 0.35% by weight of silicon dioxide (SiO2), and
[0031] - 0.005% by weight to 0.02% by weight, preferably less than 0.005% by weight to 0.01% by weight, calculated as sodium oxide (Na2O),
[0032] In another embodiment of the present invention, the ceramic substrate includes:
[0033] - The ratio of calcium content to yttrium content is greater than 0.08, preferably greater than 0.09, more preferably greater than 0.1, and the calcium and yttrium contents are calculated based on their oxide compounds (CaO / Y2O3).
[0034] In another embodiment of the present invention, the ceramic substrate includes:
[0035] - The ratio of silicon content to sodium content is greater than 10, preferably greater than 15, more preferably greater than 20, and the silicon and sodium contents are calculated based on their oxide compounds (SiO2 / Na2O).
[0036] In another embodiment of the present invention, the ceramic substrate includes:
[0037] - The ratio of silicon content to calcium content is less than 10, preferably less than 8, more preferably less than 7, and the silicon and calcium contents are calculated based on their oxide compounds (SiO2 / CaO).
[0038] In another embodiment of the present invention, the ceramic substrate includes:
[0039] - The ratio of sodium content to calcium content is less than 1.0, preferably less than 0.8, more preferably less than 0.3, and the sodium and calcium contents are calculated based on their oxide compounds (Na2O / CaO).
[0040] In yet another embodiment of the present invention, the ceramic substrate includes:
[0041] - The ratio of potassium content to calcium content is less than 1.0, preferably less than 0.8, more preferably less than 0.3, wherein the potassium and calcium contents are calculated based on their oxide compounds (Na₂O / CaO).
[0042] - The ratio of calcium content to yttrium content is greater than 0.08, preferably greater than 0.09, more preferably greater than 0.1, wherein the calcium and yttrium contents are calculated based on their oxide compounds (CaO / Y2O3), and
[0043] - The ratio of silicon content to sodium content is greater than 10, preferably greater than 15, more preferably greater than 20, wherein the silicon and sodium contents are calculated based on their oxide compounds (SiO2 / Na2O), and
[0044] - The ratio of silicon content to calcium content is less than 10, preferably less than 8, more preferably less than 7, wherein the silicon and calcium contents are calculated based on their oxide compounds (SiO2 / CaO), and
[0045] - The ratio of sodium content to yttrium content is less than 0.07, preferably less than 0.05, more preferably less than 0.03, and the sodium and yttrium contents are calculated based on their oxide compounds (Na2O / Y2O3).
[0046] The ceramic substrate of the present invention is characterized by good thermal stability and good mechanical strength, as shown by the data provided below.
[0047] Another feature of the ceramic substrate of the present invention is that the surface roughness is less than 0.5 μm, preferably less than 0.4 μm, more preferably less than 0.2 μm, for example 0.19 μm. The surface roughness further enhances the adhesion of the metal layer, and thus improves the temperature cycling stability and mechanical stability of the formed electronic compound.
[0048] The ceramic substrate of the present invention has a dense crystal arrangement and consists of two crystalline phases: ZrO2 and Al2O3 grains. The ZrO2 grains are tetragonal or monoclinic, and preferably, when measured by XRD and evaluated by the Riethveld refinement method, more than 50% provide a tetragonal crystal structure.
[0049] Yttrium oxide is included as a stabilizer in commercially available zirconium oxide. In addition to yttrium oxide, commercially available zirconium oxide also contains hafnium oxide (HfO2). HfO2 may be present in amounts ranging from not less than 1 part by weight and not more than 3 parts by weight per 100 parts of zirconium oxide. Yttrium oxide may be present in zirconium oxide in an amount of up to 6% by weight, preferably from about 5% by weight to 5.5% by weight. Preferably, 2.5 mol% to 3.5 mol% of Y2O3 (based on the amount of ZrO2) acts as a stabilizer for ZrO2. Commercially available zirconium oxide also contains additional components, such as up to 0.55% by weight of alumina (Al2O3).
[0050] The ceramic substrate of the present invention further comprises a sintering agent, particularly silicon dioxide (SiO2) and a calcium compound, preferably a calcium oxide compound, more preferably a compound selected from the list of CaO and / or CaCO3 and / or Ca(OH)2, or a mixture thereof, particularly preferably CaCO3. In a preferred embodiment of the invention, SiO2 is added in an amount of up to 0.5% by weight, preferably up to 0.4% by weight, more preferably up to 0.35% by weight. The SiO2 preferably has a 10 μm... 2 / g to 100 m 2 / g, preferably 30m 2 / g to 70 m 2 The specific surface area of / g when measured and evaluated using the BET method and the SiO2 purity of >96% by weight, preferably >99% by weight.
[0051] In a preferred embodiment of the invention, the added calcium compound is provided in an amount of up to 1.8% by weight, preferably up to 0.9% by weight, more preferably up to 0.36% by weight, and preferably has a particle size d50 of 0.1 μm to 1.2 μm, more preferably 0.2 μm to 0.75 μm, and a CaCO3 purity of >95%, more preferably >98%.
[0052] The ceramic substrate of the present invention also contains additional chemical elements such as sodium and / or magnesium. These additional chemical elements may be derived as contaminants from other components such as alumina, zirconium oxide, silicon dioxide, CaO and / or CaCO3, and / or may be added as raw materials to the raw material mixture.
[0053] In a preferred embodiment of the invention, the sodium contaminant content is known for the inorganic raw material compound, and the Na₂O / CaO and / or SiO₂ / Na₂O and / or Na₂O / Y₂O₃ content ratios are adjusted by the amount of added calcium compound and / or silicon dioxide and / or yttrium oxide. The yttrium content can be controlled by adding yttrium oxide or by adding yttrium-stabilized zirconium oxide.
[0054] In one embodiment, the flexural strength of the ceramic substrate (measured according to ASTM C1499-15) is greater than 620 MPa, preferably greater than 650 MPa.
[0055] In another embodiment, the thermal conductivity of the ceramic substrate (measured at 20°C according to ISO 18755:2005) is greater than 20 W / m*K, preferably greater than 22 W / m*K, and even more preferably greater than 24 W / m*K. The thermal conductivity can be in the range of 20 W / m*K to 40 W / m*K, preferably 21 W / m*K to 35 W / m*K, and more preferably 22 W / m*K to 30 W / m*K.
[0056] The ZTA ceramic substrate has an elastic modulus or E-modulus (Young's modulus) greater than 310 GPa, preferably greater than 350 GPa, and even more preferably greater than 360 GPa, as determined in the Grindosonic method (described in the experimental section). The E-modulus can be in the range of 310 GPa to 400 GPa, preferably in the range of 330 GPa to 390 GPa, and more preferably in the range of 350 GPa to 380 GPa.
[0057] If the fracture toughness K of the ceramic substrate (measured according to the IF method as described in the experimental section) Ic Niihara is 3 MPa m 1 / 2 Up to 5 MPa m 1 / 2 Preferably 3.5 MPa m 1 / 2 Up to 4.5 MPa m 1 / 2 More preferably 3.8 MPa m 1 / 2 Up to 4.2 MPa m 1 / 2 Further preferred is a ceramic substrate with a Vickers hardness of 1500 HV to 2000 HV, preferably 1600 HV to 1900 HV, more preferably 1700 HV to 1850 HV, and even more preferably 1750 HV to 1830 HV.
[0058] If the surface roughness Ra of the ceramic substrate (measured according to DIN EN ISO 4288) is less than 0.5 μm, preferably less than 0.4 μm, more preferably less than 0.2 μm, for example 0.19 μm, it is also preferred.
[0059] The ceramic substrate has a bulk density (measured according to DIN 993-1 / ISO 18754) greater than 3.5 g / cm³. 3 Preferably greater than 3.95 g / cm³ 3 Even more preferred is greater than 4 g / cm 3 For example, 4.0 g / cm³ to 4.1 g / cm³ 3 .
[0060] In another embodiment, the electrical breakdown strength of the ceramic substrate (measured at 20°C according to DIN EN 60243 ff) is greater than 20 kV / mm, preferably greater than 25 kV / mm, and more preferably greater than 30 kV / mm. The electrical breakdown strength can be in the range of 20 kV / mm to 40 kV / mm, preferably in the range of 25 kV / mm to 35 kV / mm, and more preferably in the range of 28 kV / mm to 33 kV / mm.
[0061] The ceramic substrate can be obtained by a method including the following steps:
[0062] - Provides at least one type of alumina, wherein the particle size d50 of said at least one type of alumina is from 0.1 μm to 1.7 μm, preferably from 0.3 μm to 1.5 μm.
[0063] - Provides at least one type of zirconium oxide, wherein the particle size d50 of said at least one type of zirconium oxide is from 0.2 μm to 1.4 μm, preferably from 0.25 μm to 1.25 μm.
[0064] - Provide silicon dioxide, said silicon dioxide having a 10 μm 2 / g to 100 m 2 / g, preferably 30 m 2 / g to 70 m 2 The specific surface area and SiO2 purity of >96% by weight, preferably >99% by weight, when measured and evaluated using the BET method.
[0065] - Provides calcium compounds such as CaO and / or CaCO3, wherein the ratio of sodium content to calcium content in the sintered ceramic substrate is less than 1.0, preferably less than 0.8, more preferably less than 0.3, said sodium and calcium contents being calculated based on their oxide compounds (Na2O / CaO).
[0066] - Combine alumina, zirconium oxide, silicon oxide, and calcium compounds and disperse the mixture in a mill.
[0067] - A mixture of alumina, zirconium oxide, silicon oxide, and calcium compound is milled to a grain size distribution difference d90-d10 of 1.70 μm to 2.20 μm, preferably 1.75 μm to 2.15 μm, more preferably 1.80 μm to 2.10 μm; a grain size distribution difference d50-d10 of 0.50 μm to 0.80 μm, preferably 0.55 μm to 0.75 μm, more preferably 0.60 μm to 0.70 μm; and a grain size distribution difference d90-d50 of 1.10 μm to 1.60 μm, preferably 1.15 μm to 1.55 μm, more preferably 1.20 μm to 1.50 μm.
[0068] - Add a binder, such as polyvinyl alcohol (PVA) or polyvinyl butyral (PVB), to the dispersed mixture of alumina and zirconium oxide.
[0069] - To shape a dispersed mixture of alumina, zirconium oxide, silica, calcium compounds, and a binder into a desired form, preferably sheet or plate form, and
[0070] - The desired form is debinding and sintered through at least one heat treatment to provide a ceramic substrate.
[0071] The ceramic substrate can also be obtained through a method including the following steps:
[0072] - A mixture of at least one type of alumina and at least one type of alumina is provided, wherein the particle size d50 of the at least one type of alumina is 0.1 μm to 0.8 μm, preferably 0.3 μm to 0.6 μm, and the particle size d50 of the at least one type of alumina is 0.9 μm to 1.7 μm, preferably 1.0 μm to 1.5 μm.
[0073] - A mixture of at least one type of zirconium oxide and at least one type of zirconium oxide is provided, wherein the particle size d50 of the at least one type of zirconium oxide is 0.2 μm to 0.5 μm, preferably 0.25 μm to 0.35 μm, and the particle size d50 of the at least one type of zirconium oxide is 0.8 μm to 1.4 μm, preferably 0.9 μm to 1.25 μm.
[0074] - Provide silicon dioxide, said silicon dioxide having a 10 μm 2 / g to 100 m 2 / g, preferably 30 m 2 / g to 70 m 2 The specific surface area and SiO2 purity of >96% by weight, preferably >99% by weight, when measured and evaluated using the BET method.
[0075] - Provides calcium compounds such as CaO and / or CaCO3, wherein the ratio of sodium content in the raw material mixture to calcium content in the raw material mixture is less than 1.0, preferably less than 0.8, more preferably less than 0.3, said sodium and calcium contents being calculated based on their oxide compounds (Na2O / CaO).
[0076] - Combine alumina, zirconium oxide, silica, and calcium compounds, and disperse the mixture in a mill.
[0077] - A mixture of alumina, zirconium oxide, silicon oxide, and calcium compound is milled to a grain size distribution difference d90-d10 of 1.70 μm to 2.20 μm, preferably 1.75 μm to 2.15 μm, more preferably 1.80 μm to 2.10 μm; a grain size distribution difference d50-d10 of 0.50 μm to 0.80 μm, preferably 0.55 μm to 0.75 μm, more preferably 0.60 μm to 0.70 μm; and a grain size distribution difference d90-d50 of 1.10 μm to 1.60 μm, preferably 1.15 μm to 1.55 μm, more preferably 1.20 μm to 1.50 μm.
[0078] - Add a binder, such as polyvinyl alcohol (PVA) or polyvinyl butyral (PVB), to the dispersed mixture of alumina and zirconium oxide.
[0079] - To shape a dispersed mixture of alumina, zirconium oxide, silica, calcium compounds, and a binder into a desired form, preferably sheet or plate form, and
[0080] - The desired form is debonded and sintered through at least one heat treatment to provide a ceramic substrate.
[0081] In one embodiment of this method, at least one grade of alumina may have a particle size of d50 of 0.1 μm to 1.7 μm, preferably 0.3 μm to 1.5 μm, and d90 of less than 4.0, preferably less than 3.6 μm.
[0082] In another embodiment of this method, the particle size d50 of at least one type of zirconium oxide is from 0.2 μm to 1.4 μm, preferably from 0.25 μm to 1.25 μm.
[0083] The first-grade Al2O3 can have a particle size of d50 of 0.3 μm to 0.6 μm and d90 of less than 3.0, preferably less than 2.0 μm, and the second-grade Al2O3 can have a particle size of d50 of 1.0 μm to 1.5 μm and d90 of less than 4.0, preferably less than 3.6 μm.
[0084] In another embodiment of this method, the first-grade Al2O3 may have a particle size of d50 of 0.3 μm to 0.6 μm and d90 of less than 3.0, preferably less than 2.0 μm, and the second-grade Al2O3 may have a particle size of d50 of 1.0 μm to 1.5 μm and d90 of less than 4.0, preferably less than 3.6 μm.
[0085] In another embodiment of this method, the first-grade ZrO2 may have a particle size of d50 of 0.25 μm to 0.35 μm and d98 of less than 2.0 μm, and the second-grade ZrO2 may have a particle size of d50 of 0.9 μm to 1.25 μm and d80 of 1.5 μm to 2.2 μm.
[0086] In one embodiment of this method, the following mixture is provided as an alumina starting material:
[0087] - 42.5% to 47.5% by weight, preferably 44% to 46.5% by weight, more preferably 44.5% to 45.5% by weight of at least one type of alumina of the first type, wherein the particle size d50 of the at least one type of alumina is 0.1 μm to 0.8 μm, preferably 0.3 μm to 0.6 μm, and
[0088] - 42.5% to 47.5% by weight, preferably 44% to 46.5% by weight, more preferably 44.5% to 45.5% by weight of at least one type of alumina of the second type, wherein the particle size d50 of the at least one type of alumina is 0.9 μm to 1.7 μm, preferably 1.0 μm to 1.5 μm.
[0089] Therefore, it is preferable to provide two types of alumina with different particle sizes and used as starting materials in a weight ratio of about 1:1, that is, about 50% by weight of each type.
[0090] In another embodiment of this method, the following mixture is provided as a zirconium oxide starting material:
[0091] - 1.2 wt% to 4.2 wt%, 1.8 wt% to 3.3 wt%, 2.4 wt% to 3 wt% of at least one type of zirconium oxide, wherein the at least one type of zirconium oxide has a particle size d50 of 0.2 μm to 0.5 μm, preferably 0.25 μm to 0.35 μm, and
[0092] - 2.8% to 9.8% by weight, 4.2% to 7.7% by weight, 5.6% to 7% by weight of at least one type of second-class zirconium oxide, wherein the particle size d50 of the at least one type of second-class zirconium oxide is 0.8 μm to 1.4 μm, preferably 0.9 μm to 1.25 μm.
[0093] Therefore, it is preferred to use about 30% by weight of at least one type of first zirconium oxide and about 70% by weight of at least one type of second zirconium oxide as starting materials, wherein the particle size d50 of the at least one type of first zirconium oxide is 0.2 μm to 0.5 μm, preferably 0.25 μm to 0.35 μm, and the particle size d50 of the at least one type of second zirconium oxide is 0.8 μm to 1.4 μm, preferably 0.9 μm to 1.25 μm.
[0094] In another embodiment of this method, sintering aids, such as silicon dioxide (SiO2) and / or calcium compounds such as CaO and / or CaCO3, and organic compounds such as binders (e.g., PVA or PVB) are added to the Al2O3 / ZrO2 mixture.
[0095] The powder mixture of Al2O3 / ZrO2 (containing Y2O3) / sintering aid is then added to the mill along with a solvent, preferably containing a dispersant, such as water or an organic solvent, to obtain a dispersion.
[0096] The dispersion comprising alumina, zirconium oxide, silicon oxide, calcium, and solvent is milled to a grain size distribution with a difference of d90-d10 of 1.70 μm to 2.20 μm, preferably 1.75 μm to 2.15 μm, more preferably 1.80 μm to 2.10 μm, a difference of d50-d10 of 0.50 μm to 0.80 μm, preferably 0.55 μm to 0.75 μm, more preferably 0.60 μm to 0.70 μm, and a difference of d50-d50 of 1.10 μm to 1.60 μm, preferably 1.15 μm to 1.55 μm, more preferably 1.20 μm to 1.50 μm.
[0097] In the next step, the slurry is used to obtain green sheets by a scraper method. Alternatively, granules prepared by spray drying the slurry using a spray dryer are used to obtain green sheets by powder pressing or roll compaction.
[0098] Next, the pressed product can be obtained by contouring using a metal mold or laser. Raw sheets can be used directly as pressed products, and their contours can be shaped using a laser after firing. Furthermore, considering mass production, multi-piece pressed products are preferred.
[0099] The sintering process is carried out in a furnace. The preferred sintering temperature is 1400℃ to 1700℃.
[0100] The ceramic substrate of the present invention can be used in electronic devices. Such electronic devices may include the ceramic substrate as a support, wherein a metal layer is located on one or both surfaces of the ceramic substrate. Electronic components may be disposed on the metal layer.
[0101] Electronic components disposed on a metal layer of a ceramic substrate can be used for, for example, semiconductor elements, such as insulated-gate bipolar transistors (IGBTs), intelligent power modules (IPMs), metal-oxide-semiconductor field-effect transistors (MOSFETs), LEDs, freewheeling diodes (FWDs), giant transistors (GTRs), or Schottky barrier diodes (SBDs). Furthermore, electronic components can be used as heating elements for sublimated thermal printheads or thermal inkjet printheads. Additionally, electronic components can be used for Peltier elements.
[0102] The invention will now be described in more detail with reference to the embodiments.
[0103] The following embodiments are included to illustrate certain aspects and embodiments of the invention as described in the claims. However, those skilled in the art will understand that the following description is merely illustrative and should not be construed as limiting the invention in any way.
[0104] I. Synthesis
[0105] Incoming raw material inspection is performed on the starting materials ZrO2, Al2O3, calcium compounds, and SiO2. At least one grade of both Al2O3 and ZrO2 is used to control the grain size distribution shown in the final product.
[0106] Batch preparation (slurry) is carried out in a mill. Batch preparation involves mixing raw materials (meaning ceramic starting materials and organic compounds). The slurry is cast to form a ceramic green film. The green film is cut to specific dimensions. The ceramic film is sintered at 1400°C to 1700°C.
[0107] II. Analysis
[0108] Grain size: an area measurement method applied to sintered ceramic substrates
[0109] The area measurement method used to determine the average grain size of alumina and zirconia is now described. First, the surface of a ceramic substrate 1 is mirror-polished and heat-treated at a temperature range of 50°C to 100°C lower than the firing temperature. The heat-treated surface is then used as the measurement surface and photographed using a SEM at 5000x magnification. Next, the photographed image data is analyzed using image analysis software (e.g., Win ROOF, available from Mitani Corporation). Therefore, data on the individual grain sizes of alumina and zirconia present in the image data can be obtained.
[0110] Although the ceramic substrate may contain crystals with a grain size smaller than 0.05 mm, in the analysis using image analysis software, only crystals with a grain size of at least 0.05 mm are targeted. Furthermore, when using image analysis software such as that described above, separate measurements are possible due to the tonal differences between alumina and zirconia grains.
[0111] The average equivalent circular diameter of each alumina grain, calculated from the area of each alumina grain, is the average grain size of alumina, and the average equivalent circular diameter of each zirconia grain, calculated from the area of each zirconia grain, is the average grain size of zirconia.
[0112] The standard deviation of alumina grain size can be determined using the same method as described above: the average grain size described above is determined based on alumina grain size data obtained using image analysis software.
[0113] Table 1 summarizes the chemical analysis, ratios of certain compounds, mechanical properties, thermal properties, and electrical properties of the comparative examples (CE) and the invention examples (IE).
[0114]
[0115] Table 1. Chemical, mechanical, thermal, and electrical properties of the comparative example (CE) and the invention example (IE).
[0116] As can be seen from Table 1, the flexural strength reaches a high value of over 650 MPa, while the thermal conductivity is >24 W / (m*K). Therefore, the invention combines excellent mechanical strength and good thermal conductivity.
[0117] Furthermore, the invention examples exhibited high temperature cycling stability in temperature cycling tests. All embodiments were metallized via direct copper bonding (DCB), in which the copper plate was directly bonded to the surface of the ZTA substrate. Subsequently, both embodiments were cycled between -55°C and +150°C before the metal layer was delaminated from the substrate.
[0118] As can be seen from Table 1, the temperature cycling stability of the invention example is 55% higher than that of the comparative example. This improvement is caused by the adjusted content ratio of the invention example as shown in Table 1.
Claims
1. A ceramic substrate, comprising: - 70% by weight or more of alumina (Al2O3) based on the total weight of the ceramic substrate. - Up to 30% by weight of zirconium dioxide (ZrO2) (based on the total weight of the ceramic substrate). - Calcium (Ca), sodium (Na) and yttrium (Y). - Other elements: silicon (Si) and / or magnesium (Mg). - Wherein the ratio of sodium content to yttrium content is less than 0.03, and the sodium and yttrium contents are calculated based on their oxide compounds (Na2O / Y2O3).
2. The ceramic substrate according to claim 1, comprising: - 75% to 95% by weight, preferably 88% to 93% by weight, more preferably 89% to 91% by weight of alumina (Al2O3) based on the total weight of the ceramic substrate. - 4% to 14% by weight, preferably 6% to 11% by weight, more preferably 8% to 10% by weight of zirconium dioxide (ZrO2) based on the total weight of the ceramic substrate.
3. The ceramic substrate according to any one of the preceding claims, comprising: - 0.2% to 0.8% by weight, preferably 0.3% to 0.7% by weight, more preferably 0.4% to 0.6% by weight of yttrium calculated as sesquioxide (Y₂O₃), based on the total weight of the ceramic substrate. - 0.01% to 1.0% by weight, preferably 0.02% to 0.5% by weight, more preferably 0.03% to 0.2% by weight of calcium, calculated as calcium oxide (CaO), based on the total weight of the ceramic substrate.
4. The ceramic substrate according to any one of the preceding claims, comprising: (Based on the total weight of the ceramic substrate) 0.1% to 0.5% by weight, preferably 0.2% to 0.4% by weight, more preferably 0.25% to 0.35% by weight of silicon dioxide (SiO2).
5. The ceramic substrate according to any one of the preceding claims, comprising: (Based on the total weight of the ceramic substrate) less than 0.02% by weight, preferably less than 0.01% by weight of sodium oxide (Na2O).
6. The ceramic substrate according to any one of the preceding claims, comprising: The ratio of calcium content to yttrium content is greater than 0.08, preferably greater than 0.09, and more preferably greater than 0.1, wherein the calcium content and yttrium content are calculated based on their oxide compounds (CaO / Y2O3).
7. The ceramic substrate according to any one of the preceding claims, characterized in that, The ratio of silicon content to sodium content is greater than 10, preferably greater than 15, more preferably greater than 20, and the silicon and sodium contents are calculated based on their oxide compounds (SiO2 / Na2O).
8. The ceramic substrate according to any one of the preceding claims, characterized in that, The ratio of silicon content to calcium content is less than 10, preferably less than 8, more preferably less than 7, and the silicon and calcium contents are calculated based on their oxide compounds (SiO2 / CaO).
9. The ceramic substrate according to any one of the preceding claims, characterized in that, The ratio of sodium oxide content to calcium oxide content is less than 1.0, preferably less than 0.8, more preferably less than 0.3, and the sodium oxide content and calcium oxide content are calculated based on their oxide compounds (Na2O / CaO).
10. The ceramic substrate according to any one of the preceding claims, characterized in that, The electrical breakdown strength is greater than 20 kV / mm, preferably greater than 25 kV / mm, and more preferably greater than 30 kV / mm.
11. The ceramic substrate according to any one of the preceding claims, characterized in that, The surface roughness Ra (measured according to DIN EN ISO 4288) is less than 0.5 μm, preferably less than 0.4 μm, and more preferably less than 0.2 μm.
12. A method for obtaining a ceramic substrate according to any one of the preceding claims, comprising the following steps: - Provide at least one type of alumina, - Provide at least one type of zirconium oxide, - Provides silicon dioxide, - Provides calcium compounds CaO and / or CaCO3 and / or Ca(OH)2, wherein the ratio of sodium content in the raw material mixture to calcium content in the raw material mixture is less than 1.0, preferably less than 0.8, more preferably less than 0.3, said sodium and calcium contents are calculated based on their oxide compounds (Na2O / CaO). - The alumina, zirconium oxide, silicon oxide, and calcium compound are combined and the mixture is dispersed in a mill. - Grind the mixture of the alumina, the zirconium oxide, the silicon oxide, and the calcium compound. - Add a binder to the dispersed and milled mixture. - To shape the dispersed mixture and binder into the desired form, and - The shaped mixture is sintered to provide the ceramic substrate.
13. The method for obtaining a ceramic substrate according to claim 12, wherein a mixture of at least one type of alumina and at least one type of alumina is provided, wherein the particle size d50 of the at least one type of alumina is 0.1 μm to 0.8 μm, preferably 0.3 μm to 0.6 μm, and the particle size d50 of the at least one type of alumina is 0.9 μm to 1.7 μm, preferably 1.0 μm to 1.5 μm; and / or a mixture of at least one type of zirconium oxide and at least one type of zirconium oxide, wherein the particle size d50 of the at least one type of zirconium oxide is 0.2 μm to 0.5 μm, preferably 0.25 μm to 0.35 μm, and the particle size d50 of the at least one type of zirconium oxide is 0.8 μm to 1.4 μm, preferably 0.9 μm to 1.25 μm.
14. The method for obtaining a ceramic substrate according to claims 12 to 13, wherein silicon dioxide with a particle size d50 of 0.1 μm to 1.5 μm, preferably 0.2 μm to 0.8 μm, and / or calcium compounds CaO and / or CaCO3 Ca(OH)2 with a particle size d50 of 0.1 μm to 1.2 μm, preferably 0.2 μm to 0.75 μm, are provided.
15. The method for obtaining a ceramic substrate according to claims 12 to 15, wherein the dispersed mixture and binder are shaped into a desired form by casting.
Citation Information
Patent Citations
Ceramic substrate and mounting substrate using same, and electronic device
EP3786134A1
